Cell wall and cell growth characteristics of giant‐celled algae. Issue 2 (April 2015) - Mine, Ichiro; Sekida, Satoko; Okuda, Kazuo
Summary: Because of their large sizes and simple shapes, giant‐celled algae have been used to study how the structural and mechanical properties of cell walls influence cell growth. Here we review known relationships between cell wall and cell growth properties that are characteristic of three representative taxa of giant‐celled algae, namely, Valonia ventricosa, internodal cells of characean algae, and Vaucheria frigida . Tip‐growing cells of the genus Vaucheria differ from cells undergoing diffuse growth in V. ventricosa and characean algae in terms of their basic architectures (non‐lamellate vs. multilamellate) and their dependence upon pH and Ca 2+ for cell wall extensibility. To further understand the mechanisms controlling cell growth by cell walls, comparative analyses of cell wall structures and/or associated growth modes will be useful. The giant‐celled algae potentially serve as good models for such investigations because of their wide variety of developmental processes and cell shapes exhibited.